1993
DOI: 10.1128/aac.37.12.2599
|View full text |Cite
|
Sign up to set email alerts
|

A pyrimido[1,6-a]benzimidazole that enhances DNA cleavage mediated by eukaryotic topoisomerase II: a novel class of topoisomerase II-targeted drugs with cytotoxic potential

Abstract: Recently, a number of novel quinolones with potent activity against topoisomerase H and eukaryotic cells have been described. Many of these compounds contain aromatic substituents in their C-7 ring positions. To determine whether pyrimido[1,6-albenzimidazoles, a class of drugs modeled on quinolones, also display activity toward eukaryotic systems, the effects of Ro 46-7864 and Ro 47-3359 on Drosophila melanogaster topoisomerase II and Kc cells were characterized. While the former drug contains an aliphatic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Quinolones Act by Inhibiting DNA Religation Mediated by S. aureus Topoisomerase IV-As determined by their effects on DNA religation, drugs enhance DNA cleavage mediated by type II topoisomerases by two alternative (but not mutually exclusive) mechanisms (44,45). While some drug classes strongly inhibit enzyme-mediated DNA religation, others have little effect on this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Quinolones Act by Inhibiting DNA Religation Mediated by S. aureus Topoisomerase IV-As determined by their effects on DNA religation, drugs enhance DNA cleavage mediated by type II topoisomerases by two alternative (but not mutually exclusive) mechanisms (44,45). While some drug classes strongly inhibit enzyme-mediated DNA religation, others have little effect on this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…However, a body of literature indicates that anticancer drugs targeted to eukaryotic type II topoisomerases stimulate DNA cleavage in one of two primary fashions. They act either by inhibiting the ability of the enzyme to religate cleaved DNA molecules, or by increasing rates of enzyme-mediated DNA cleavage (37,(53)(54)(55)(56)(57)(58).…”
Section: Quinolone Mechanismmentioning
confidence: 99%
“…These compounds have been described as being DNA cleaving agents [1], DNA gyrase inhibitors [2][3][4][5][6][7], antiinflammatory [8][9][10], antiamoebic and analgesic [8,9], herbicidal [11], antimicrobial and antifungal [12], antiulcer [13], polymer dye additive [14], variolin alkaloids analogues [15][16][17], and nucleoside analogues agents [18,19]. Studies on benzene carcinogenesis and mutagenesis showed that p-benzoquinone which is the oxidation product of benzene reacts with deoxycitidine in the human body [20][21][22][23][24][25][26][27] to produce a pyrimido [1,6-a]benzimidazole structure as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…These derivatives can be prepared by cyclocondensation of 1-(2-aminoaryl) urea with diethyl malonate, 2-substituted benzimidazolylacetates with carbonate esters [1][2][3][4][5][6], condensation of ketoisothiocyanates with orthophenylenediamines [8][9][10] and methyl 2-(bromomethyl)-1H-benzimidazole-1-carboxylate with tosylmethylisocyanides [15][16][17], reaction of 4-O-[(triisopropylphenyl)sulfonyl]-pyrimidine nucleosides with orthophenylenediamine [18][19] and direct or biomedia reaction of deoxycytidine with p-benzoquinone [20][21][22][23][24][25][26][27]. Other routes include condensation of 2-(3-aminopropyl)-benzimidazole with carbon disulfide [28], 2-(2-benzimidazolyl)acetonitrile and 2-(2-benzimidazolyl)ethylacetate [29][30][31][32][33][34][35][36], ring construction of pyrimido [4,5-b]- [1,5]benzodiazepines [37][38][39], reaction of 6-chloro [1,3]oxazine-2,4-diones with orthophenylenediamine [40] and cyclocondensation of (benzimidazol-2-ylmethyl)-triphenylphosphonium chloride [41][42][43].…”
Section: Introductionmentioning
confidence: 99%